A novel quantitative real-time polymerase chain reaction method for detecting toxigenic Pasteurella multocida in nasal swabs from swine. Issue 1 (December 2016) - Scherrer, Simone; Frei, Daniel; Wittenbrink, Max
Abstract Background Progressive atrophic rhinitis (PAR) in pigs is caused by toxigenicPasteurella multocida . In Switzerland, PAR is monitored by selective culture of nasal swabs and subsequent polymerase chain reaction (PCR) screening of bacterial colonies for theP. multocida toxA gene. A panel of 203 nasal swabs from a recent PAR outbreak were used to evaluate a novel quantitative real-time PCR for toxigenicP. multocida in porcine nasal swabs. Results In comparison to the conventional PCR with a limit of detection of 100 genome equivalents per PCR reaction, the real-time PCR had a limit of detection of 10 genome equivalents. The real-time PCR detectedtoxA -positiveP. multocida in 101 samples (49.8%), whereas the conventional PCR was less sensitive with 90toxA -positive samples (44.3%). In comparison to the real-time PCR, 5.4% of thetoxA -positive samples revealed unevaluable results by conventional PCR. Conclusions The approach of culture-coupledtoxA PCR for the monitoring of PAR in pigs is substantially improved by a novel quantitative real-time PCR.